Mapping the illness trajectories of insomnia: a biographical disruption?. Issue 5 (7th December 2016) - Cheung, Janet M.Y.; Saini, Bandana; Bartlett, Delwyn J.; Laba, Tracey‐Lea; Mason, Paul H.
Abstract: The insomnia illness experience can be conceptualised as a form of biographical disruption. Using a critical interpretive phenomenological lens 51 in‐depth semi‐structured interviews were conducted with patients from specialist sleep and psychology clinics ( n = 22) and the general community ( n = 29). Patients' narratives revealed key phases of their illness trajectories as they recognise, rethink and respond to insomnia. Their biographical events served as reference points for both patient groups to make sense of their illness experiences as they transitioned from a perceived state of sleeplessness to clinical insomnia. The innate biological process of sleep at night and the sleep‐dependent daytime psychosocial function exerted a negative bi‐directional effect, creating a continuous circuit of disruption. Coping mechanisms were inspired by the participants' immediate social environment and centred on sociocultural motifs of relaxation and alertness to break the 'circuit'. Access to specialist clinic services appeared to be contingent on the richness of resources in one's social network and surrounding environment rather than the clinical severity of the disease alone. Treatment that can simultaneously target the night time and daytime consequences of insomnia resonates closely with participants' depiction of insomnia as both a physiological and a psychosocial phenomenon.